Adelosgryllus rubricephalus: a new genus and species of cricket (Orthoptera: Phalangopsidae) - Mesa, Alejo [UNESP]; Zefa, Edison (Sociedade Entomológica do Brasil, 2004)
Um novo gênero e espécie de grilo falangopsídeo Adelosgryllus rubricephalus é descrito. Ilustrações de espécimes macho e fêmea e a descrição dos escleritos fálicos, assim como os cromossomos e a distribuição geográfica conhecida são relatados. Uma discussão sobre a posição taxonômica desse grilo dentro da família Phalangopsidae é incluída.

Adelosgryllus rubricephalus, a new genus and species of phalangopsid cricket are described. Illustrations of male and female specimens as well as descriptions of phallic sclerites, chromosomes and geographical known distribution are furnished. A discussion on the species taxonomic status of this cricket within the family is also included.
Adelosgryllus rubricephalus: um novo gênero e espécie de grilo (Orthoptera: Phalangopsidae)
Keywords: Grylloidea; morfologia; esclerito fálico; cromossomo; Grylloidea; morphology; phallic sclerite; chromosome